Impact behavior of gravity cast AlSi10Mg alloy: Effect of hot isostatic pressing and innovative high pressure T6 heat treatment - Luca Girelli; Maverick Giovagnoli; Marialaura Tocci; Annalisa Fortini; Marcello Gelfi; Mattia Merlin; Annalisa Pola (Fracture and Structural Integrity)
In the present study the impact behavior of gravity casting AlSi10Mg alloy was evaluated with an instrumented Charpy pendulum. The effect of hot isostatic pressing, also followed by a T6 treatment, was analyzed in comparison with samples in the as-cast, annealed and T6 conditions. Furthermore, the effect of the innovative high-pressure T6 was investigated. It was found that the hot isostatic pressing is able to ensure densification of the alloy with an increase in both hardness and energy absorbed during impact. The T6 treatment performed at atmospheric pressure after the hot isostatic pressing is able to increase hardness and peak force. At the same time, the innovative high-pressure T6 is able to ensure similar results than those of hot isostatic pressing followed by T6, leading to a significant decrease in the treatment duration and costs and reducing the carbon footprint of the manufacturing process.